Phosphate ester-based surfactants for alkaline battery anodes
The health and environmental problems of nonylphenol functional groups in the prior art are solved by using phosphate-based surfactants, including surfactants of formula (I) and (II) in the alkaline cell anode, and Inhibit zinc corrosion reaction and hydrogen generation, achieving better battery performance and environmentally friendly battery design.
Patent Information
- Application Number
- CN202380043641.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-03
- Filing Date
- 2023-06-05
- Publication Date
- 2025-02-07
AI Technical Summary
Surfactants in existing alkaline battery anodes contain nonylphenol functional groups, which are concerned by health and environmentally friendly, and are difficult to inhibit zinc corrosion reactions and hydrogen generation, while increasing the load of electrochemically active materials alone is limited by the battery size and internal volume. .
Using phosphate-based surfactants, specifically including a composition of zinc or zinc alloys with surfactants of formula (I) and formula (II), the surfactants in formula (I) are composed of aryl, phosphate and specific couples. The connecting ring system consists of which the surfactant in formula (II) contains methyl or hydrogen and a macrocyclic coupling ring system, which is used to form a protective layer on the zinc particles to inhibit corrosion and hydrogen generation.
Effectively inhibit zinc corrosion reaction and hydrogen generation, provide better discharge capacity and battery performance, and does not contain nonylphenol functional groups, meeting health and environmental requirements.
Smart Images

Figure CN119404327A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Patent Application Serial No. 63 / 348,867, filed on June 3, 2022, under 35 U.S.C. §119(e), the entire disclosure of which is incorporated herein by reference. Technical Field
[0003] The present disclosure relates to phosphate-based surfactants for alkaline battery anodes and anodes and batteries including the surfactants. Background Art
[0004] Electrochemical cells or batteries are commonly used as a source of electrical energy. The battery contains a negative electrode, commonly referred to as an anode, and a positive electrode, commonly referred to as a cathode. The anode contains an electrochemically active anode material that can be oxidized. The cathode contains an electrochemically active cathode material that can be reduced. The electrochemically active anode material is capable of reducing the electrochemically active cathode material. A separator is disposed between the anode and cathode, and an ionically conductive electrolyte solution is in intimate contact with the cathode, anode, and separator. The battery components are housed in a can or housing, which is typically made of metal.
[0005] When a battery is used as an electrical energy source in an electronic device, the anode and cathode are in electrical contact, allowing electrons to flow through the device and allowing corresponding oxidation and reduction reactions to occur to provide electrical energy to the electronic device. The electrolyte contains ions that flow through the separator between the anode and cathode to maintain charge balance throughout the battery during discharge.
[0006] There is an increasing need to prepare batteries that are better suited for powering contemporary electronic devices such as toys; remote controls; audio devices; flashlights; digital cameras and peripheral photography equipment; electronic games; toothbrushes; radios; and clocks. To meet this demand, batteries can contain higher loadings of electrochemically active anode and / or cathode materials to provide increased capacity and service life. However, batteries also come in common sizes, such as AA, AAA, AAAA, C, and D cell sizes, which have fixed outer dimensions and restricted internal volumes. Therefore, the ability to increase the loading of electrochemically active materials alone to achieve better performing batteries is limited.
[0007] The composition of the anode can be adjusted to provide enhanced performance. For example, a surfactant can be included in the anode composition to produce a protective layer around the zinc particles, thereby inhibiting zinc corrosion reactions and the formation of hydrogen gas, which can be generated when the battery cell including the anode is resting. The surfactant can adhere to the surface of the zinc anode particles, inhibiting hydroxide ions or water from approaching the zinc particles, thereby inhibiting zinc corrosion and the formation of hydrogen gas (reactions (I) and (II)) from occurring on the surface of the zinc particles.
[0008] Zn+4OH - →Zn(OH)4 2- +2e - (I)
[0009] 2H2O+2e - →2OH - +H2(II)
[0010] Phosphate-based surfactants including polyoxyethylene dinonylphenyl ether phosphate are commonly used in battery anode compositions; however, such commonly used phosphate materials contain nonylphenol functional groups, which are regulated in some countries due to health and environmental concerns. Therefore, surfactants that inhibit zinc corrosion reactions and the accompanying formation of hydrogen gas and do not contain nonylphenol functional groups are desirable. Summary of the invention
[0011] One aspect of the present disclosure provides an anode composition, the anode composition comprising zinc or a zinc alloy and a surfactant of formula (I):
[0012]
[0013] wherein R1 comprises an aryl group; x is an integer from 2 to 30; n is an integer from 2 to 6; and y is 1 or 2. The aryl group of the surfactant may be selected from phenyl, naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, perylenyl and biphenyl.
[0014] Another aspect of the present disclosure provides an anode composition, the anode composition comprising zinc or a zinc alloy and a surfactant of formula (II):
[0015]
[0016] wherein R is methyl or hydrogen; x is an integer from 2 to 30, and rings 1 and 2 represent a coupled ring system comprising at least 10 ring carbons. The coupled ring system may be naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, perylenyl, biphenyl or bicyclohexyl.
[0017] Another aspect of the present disclosure provides an alkaline battery, the alkaline battery comprising an electrochemically active anode, the electrochemically active anode comprising zinc or a zinc alloy and a surfactant of formula (I):
[0018]
[0019] wherein R1 comprises an aryl group; x is an integer from 2 to 30; n is an integer from 2 to 6; and y is 1 or 2. The aryl group of the surfactant may be selected from phenyl, naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, and perylenyl.
[0020] Yet another aspect of the present disclosure provides an alkaline battery, the alkaline battery comprising an electrochemically active anode, the electrochemically active anode comprising zinc or a zinc alloy and a surfactant of formula (II):
[0021]
[0022] wherein R is methyl or hydrogen; x is an integer from 2 to 30, and rings 1 and 2 represent a coupled ring system comprising at least 10 ring carbons. The coupled ring system may be naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, perylenyl, biphenyl or bicyclohexyl.
[0023] Another aspect of the present disclosure provides a method for preparing a battery anode, the method comprising mixing zinc or a zinc alloy with a surfactant of formula (I):
[0024]
[0025] wherein R1 comprises an aryl group; x is an integer from 2 to 30; n is an integer from 2 to 6; and y is 1 or 2. The aryl group of the surfactant may be selected from phenyl, naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, and perylenyl.
[0026] Another aspect of the present disclosure provides a method for preparing a battery anode, the method comprising mixing zinc or a zinc alloy with a surfactant of formula (II):
[0027]
[0028] wherein R is methyl or hydrogen; x is an integer from 2 to 30, and rings 1 and 2 represent a coupled ring system comprising at least 10 ring carbons. The coupled ring system may be naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, perylenyl, biphenyl or bicyclohexyl.
[0029] Yet another aspect of the present disclosure provides a method of preparing a battery, the method comprising incorporating into the battery an anode comprising zinc or a zinc alloy and a surfactant of formula (I):
[0030]
[0031] wherein R1 comprises an aryl group; x is an integer from 2 to 30; n is an integer from 2 to 6; and y is 1 or 2. The aryl group of the surfactant may be selected from phenyl, naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, and perylenyl.
[0032] In a further aspect, the present disclosure provides a method of preparing a battery, the method comprising incorporating into the battery an anode comprising zinc or a zinc alloy and a surfactant of formula (II):
[0033]
[0034] wherein R is methyl or hydrogen; x is an integer from 2 to 30, and rings 1 and 2 represent a coupled ring system comprising at least 10 ring carbons. The coupled ring system may be naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, perylenyl, biphenyl or bicyclohexyl.
[0035] By reviewing the following detailed description, additional aspects and advantages will become apparent to those of ordinary skill in the art. Although the compositions and methods may have various forms of embodiments, the following description includes specific embodiments under the understanding that the present disclosure is illustrative and is not intended to limit the present disclosure to the specific embodiments described herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] While the specification concludes with claims particularly pointing out and distinctly claiming the subject matter regarded as forming the present invention, the present invention will be better understood from the following description taken in conjunction with the accompanying drawings.
[0037] Figure 1 is a side cross-sectional view of one embodiment of a battery including an anode comprising a surfactant according to the present invention.
[0038] Figure 2 is a continuous cell discharge curve showing voltage versus time for a cell including an anode including a surfactant according to the present invention and a control cell including an anode not including a surfactant.
[0039] Figure 3 is an intermittent pulse cell discharge curve showing voltage versus capacity for a cell including an anode including a surfactant according to the present invention and a control cell including an anode not including a surfactant. DETAILED DESCRIPTION
[0040] The present disclosure provides an anode composition, an alkaline battery, a method for preparing a battery anode, and a method for preparing a battery, wherein the anode comprises zinc or a zinc alloy and a surfactant of formula (I):
[0041]
[0042] wherein R1 comprises an aryl group; x is an integer from 2 to 30; n is an integer from 2 to 6; and y is 1 or 2. The aryl group of the surfactant may be selected from phenyl, naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl and peryl. The aryl group may optionally be further substituted with one or more substituents, specifically substituents that increase solubility in aqueous solution.
[0043] Another aspect of the present disclosure provides an anode composition, the anode composition comprising zinc or a zinc alloy and a surfactant of formula (II):
[0044]
[0045] wherein R is methyl or hydrogen; x is an integer from 2 to 30, and rings 1 and 2 represent a coupled ring system comprising at least 10 ring carbons. Non-limiting examples of coupled ring systems include fused cyclohexyl rings and fused benzene rings, but other rings may also be used. The coupled ring system may be naphthyl, fluorenyl, anthracenyl, phenanthrenyl, tetraphenyl, benzo[a]anthryl, pyrenyl, perylenyl, biphenyl or bicyclohexyl. The coupled ring system may optionally be further substituted with one or more substituents, specifically substituents that increase solubility in aqueous solution.
[0046] The anodes of the present disclosure and batteries including the anodes of the present disclosure advantageously provide one or more benefits, for example, providing a zinc anode including zinc particles and having a protective surfactant layer around the zinc particles, the protective surfactant layer inhibiting both zinc corrosion reactions and the generation of hydrogen gas, and / or providing a battery with good discharge capacity, advantageously without containing nonylphenol functional groups.
[0047] refer to Figure 1, the battery 10 according to the present invention comprises a cathode 12, an anode 14, a separator 16 and a cylindrical housing 18. The battery 10 also comprises a current collector 20, a seal 22 and a negative metal top cover 24, which serves as a negative terminal of the battery. The cathode 12 is in contact with the housing 18, and the positive terminal of the battery 10 is located at the end of the battery opposite to the negative terminal. The alkaline electrolyte is dispersed throughout the battery 10. The battery 10 can be, for example, an AA, AAA, AAAA, C or D battery. Although the battery 10 can be cylindrical, in some embodiments, the battery 10 can be non-cylindrical. For example, the battery 10 can be a button cell, a button cell or a wafer cell. In some embodiments, the battery can be prismatic. In some embodiments, the battery can have a rigid layered cell configuration, or be provided in a flexible bag, envelope or pouch cell configuration. In some embodiments, the battery can have a spirally wound jelly roll configuration, or a flat plate configuration. Suitable cells are described, for example, in US Pat. Nos. 6,783,893; 7,435,395 and US Patent Application Publication No. 2007 / 0248879.
[0048] anode
[0049] Anode 14 can be, for example, a zinc gel comprising zinc metal particles, one or more gelling agents, one or more surfactants, and optionally a small amount of additives. In addition, a portion of the electrolyte solution is dispersed throughout the anode. The zinc metal particles can include zinc (elemental metal). The zinc metal particles can be a zinc alloy and further include one or more metals, for example, one or more selected from the following groups: aluminum, bismuth, calcium, gallium, indium, lithium, magnesium, lead and tin. The zinc metal particles can have a size in the range of 45 to 350 μm and a median particle size in the range of 80 to 255 μm, as determined by CCD imaging measurements. Zinc metal particles, generally referred to as "fine particles" having a size of 44 microns or less, can be included to increase the surface area of zinc in the anode. The zinc fines may be included in an amount of about 1 wt.% to about 30 wt.%, about 5 wt.% to about 30 wt.%, about 10 wt.% to about 25 wt.%, for example, about 5 wt.%, about 10 wt.%, about 15 wt.%, about 20 wt.%, about 25 wt.%, or about 30 wt.%, based on the total weight of the zinc metal particles.
[0050] The term "about" is used according to its ordinary meaning, for example, to mean approximately or about. In one embodiment, the term "about" means the value or range of values ± 10%. In another embodiment, the term "about" means the value or range of values ± 5%. The value or range described in conjunction with the term "about" also explicitly includes specific values and / or ranges (for example, for a value described as "about 40", "40" is also explicitly considered). Further, the dimensions and values disclosed herein should not be understood to be strictly limited to the exact numerical values listed. On the contrary, unless otherwise specified, each such dimension is intended to represent both the stated value and the functionally equivalent range around the value.
[0051] The amount of electrochemically active anode material in the anode can be referred to as the anode load. The load of the anode can vary according to the electrochemically active anode material used in the battery and the battery cell size of the battery. For example, an AA battery with a zinc electrochemically active anode material can have at least about 3.3 grams of zinc metal particles, such as at least about 4.0, about 4.3, about 4.6 grams, about 5.0 grams, or about 5.5 grams of zinc metal particles. For example, a AAA battery with a zinc electrochemically active anode material can have at least about 1.9 grams of zinc metal particles, such as at least about 2.0 or about 2.1 grams of zinc metal particles. For example, an AAAA battery with a zinc electrochemically active anode material can have at least about 0.6 grams of zinc metal particles, such as at least about 0.7 to about 1.0 grams of zinc metal particles. For example, a C battery with a zinc electrochemically active anode material can have at least about 9.5 grams of zinc metal particles, such as at least about 10.0 to about 15.0 grams of zinc metal particles. For example, a D cell having a zinc electrochemically active anode material can have an anode loading of at least about 19.5 grams of zinc metal particles, such as at least about 20.0 to about 30.0 grams of zinc metal particles.
[0052] The anode typically includes a gelling agent. Examples of gelling agents include polyacrylic acid, polyacrylonitrile, starch, starch derivatives, grafted starch materials (e.g., starch grafted polyacrylic acid, starch grafted polyacrylonitrile), polyacrylic acid salts, polyacrylates, cellulose derivatives, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid cross-linked with a polyalkenyl ether of diethylene glycol; or combinations thereof. The anode may include, for example, about 0.1 wt % to about 2 wt % of a gelling agent.
[0053] The surfactants of the present disclosure may include surfactants according to formula (I):
[0054]
[0055] wherein R1 comprises an aryl group; x is an integer from 2 to 30; n is an integer from 2 to 6; and y is 1 or 2. The aryl group of the surfactant may be selected from phenyl, naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl and perylenyl. In one embodiment, R1 is 2-naphthyl.
[0056] Formula (I) surfactant is usually provided as a mixture of surfactants with formula (I). Usually, y can be selected from 1 or 2. Therefore, in some embodiments, the surfactant includes a phosphoric acid monoester (that is, when y is 1) or a phosphoric acid diester (that is, when y is 2). In other embodiments, the phosphate ester surfactant includes a mixture of a phosphoric acid monoester and a phosphoric acid diester surfactant according to formula (I). When y is 2, x and n occur twice and can vary independently, i.e., each x can be the same or different, and each n can be similarly the same or different.
[0057] In formula (I), x can be any integer in the range of 2 to 30, 3 to 25, 5 to 20, 8 to 20, 10 to 18, or 12 to 16, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30. In embodiments, the surfactant of formula (I) comprises a mixture of surfactants of formula (I), and the average x value of the mixture is in the range of 2 to 30, 3 to 25, 5 to 20, 8 to 20, 10 to 18, or 12 to 16, for example 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30. In embodiments, the surfactant of formula (I) is provided as a mixture, and the average x of the mixture is in the range of 6 to 16, 8 to 16, or 8 to 14. Without intending to be bound by theory, it is believed that as the value of x (or the average value of x) decreases, the solubility of the surfactant in the electrolyte decreases. Further, without intending to be bound by theory, it is believed that as the value of x (or the average value of x) increases, the solubility of the surfactant increases, followed by an increase in the association of the chain with other surfactant molecules and / or other materials, and / or the mass of the surfactant becomes too large and eventually decreases. Advantageously, when x is in the range of 6 to 16, 8 to 16, or 8 to 14, significantly less surfactant can be used compared to an anode comprising a conventional polyoxyethylene dinonylphenyl ether phosphate surfactant, while advantageously providing substantially the same performance. Because less surfactant is included, a lower addition volume is used, allowing the inclusion of additional electrochemically active anode materials, further enhancing performance relative to an anode comprising a conventional polyoxyethylene dinonylphenyl ether phosphate surfactant.
[0058] In formula (I), n can be any integer integer in the range of 2 to 6, such as 2, 3, 4, 5, or 6. In an embodiment, n is in the range of 2 to 3. For example, n can be 2 or 3. Typically, n is 2. Without intending to be bound by theory, it is believed that as the value of n increases, the solubility of the surfactant in the electrolyte decreases.
[0059] The surfactants of the present disclosure may include surfactants according to formula (II):
[0060]
[0061] wherein R is methyl or hydrogen; x is an integer from 2 to 30, and rings 1 and 2 represent a coupled ring system comprising at least 10 ring carbons. The coupled ring system may be naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, perylenyl, biphenyl or bicyclohexyl.
[0062] The surfactant of formula (II) is usually provided as a mixture of surfactants having formula (I). In formula (II), x occurs twice and may vary independently, ie each x may be the same or different.
[0063] In formula (II), x can be any integer in the range of 2 to 30, 3 to 25, 5 to 20, 8 to 20, 10 to 18, or 12 to 16, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30. In an embodiment, the surfactant of formula (II) comprises a mixture of surfactants of formula (II), and the average x value of the mixture is in the range of 2 to 30, 3 to 25, 5 to 20, 8 to 20, 10 to 18, or 12 to 16, for example 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30. In an embodiment, the surfactant of formula (II) is provided as a mixture, and the average x of the mixture is in the range of 6 to 16, 8 to 16, or 8 to 14. Without intending to be bound by theory, it is believed that as the value of x (or the average value of x) decreases, the solubility of the surfactant in the electrolyte decreases. Further, without intending to be bound by theory, it is believed that with the increase of x value (or the average value of x), the solubility of the surfactant increases, which is then increased due to the association of the chain with other surfactant molecules and / or other materials, and / or the mass of the surfactant becomes too large and eventually decreases. Advantageously, when x is in the range of 12 to 16, significantly less surfactant can be used compared to the anode comprising conventional polyoxyethylene dinonylphenyl ether phosphate surfactants, while advantageously providing substantially the same performance. Because less surfactant is included, a lower addition volume is used so that additional electrochemically active anode materials can be included, further enhancing performance relative to the anode comprising conventional polyoxyethylene dinonylphenyl ether phosphate surfactants. Additionally, adding a lower volume of surfactant can beneficially cause less rupture of the pregelatinized anode, and therefore produce a higher yield stress anode.
[0064] The surfactant according to formula (I) and / or (II) is included in the anode composition to produce a protective layer around the zinc particles to inhibit the zinc corrosion reaction, but must be able to dissociate from the surface of the zinc particles to allow the discharge reaction to proceed. The surfactant according to formula (I) and / or (II) can be included in the anode composition in an amount ranging from about 10 ppm to about 75 ppm, about 10 ppm to about 65 ppm, about 10 ppm to about 55 ppm, about 10 ppm to about 50 ppm, about 20 ppm to about 50 ppm, or about 20 ppm to about 45 ppm relative to the amount of zinc in the anode composition, for example, the surfactant can be included in the anode composition in an amount of about 10 ppm, about 15 ppm, about 20 ppm, about 25 ppm, about 30 ppm, about 35 ppm, about 40 ppm, about 45 ppm, or about 50 ppm relative to the amount of zinc metal particles in the anode composition. The amount of the surfactant according to formula (I) and / or (II) is provided in parts per million relative to the amount of zinc metal particles. Thus, for every one million parts by weight of zinc metal particles, there are, for example, 10 to 75 parts by weight of a surfactant according to formula (I) and / or (II). The surfactant according to formula (I) and / or (II) can be diluted to 1% in a 0.05M alkaline hydroxide, such as a KOH solution, to allow for more precise addition of amounts to the anode composition. Without intending to be bound by theory, it is believed that as the level of surfactant increases relative to the amount of zinc metal particles in the anode, the surface passivation of the zinc anode increases. Therefore, more energy will be required to remove the surfactant molecules from the surface of the zinc metal particles to allow the discharge reaction to proceed. Without intending to be bound by theory, it is believed that the increase in surface passivation may be due to an excessively thick surfactant monolayer on the surface of the anode, the formation of multilayer surfactant micelles on the surface of the anode, or a combination thereof. Advantageously, as shown in the examples provided below, the surfactant according to formula (I) and / or (II) can provide suitable surface coverage of the zinc anode using less surfactant than typical commercial surfactants, thereby requiring less energy to remove the surfactant from the anode surface to allow the discharge reaction to proceed. Of course, the surfactant can also be used at higher levels.
[0065] Advantageously, the surfactant according to formula (I) and (II) does not contain nonylphenol functional groups. As used herein, "does not contain nonylphenol functional groups" means that the surfactant does not contain nonylphenol functional groups and / or the anode composition comprising the surfactant does not contain a significant amount of surfactant with nonylphenol functional groups. Therefore, incidental or background amounts of surfactant with nonylphenol functional groups (e.g., less than about 100 ppb) may be present in the surfactant and / or anode composition and are within the scope of the present disclosure.
[0066] Additionally, surfactant coverage of zinc particles by surfactant can have an impact on the performance decay of a battery including the surfactant. Without intending to be bound by theory, it is believed that the faster the surfactant reaches maximum surface coverage of the zinc metal particles of the anode, the less performance capacity decay exhibited by a battery including the anode because the time the zinc metal particles are directly exposed to the electrolyte is minimized. Battery performance capacity can be measured using various known techniques, including but not limited to those described below.
[0067] Electrolytes
[0068] The electrolyte can be dispersed throughout the cathode, anode and separator. The electrolyte includes an ion-conducting component in an aqueous solution. The ion-conducting component can be a hydroxide. The hydroxide can be, for example, sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide or a mixture thereof. The ion-conducting component can further include a salt. The salt can be, for example, zinc chloride, ammonium chloride, magnesium perchlorate, magnesium bromide and a mixture thereof. The concentration of the ion-conducting component can be selected according to the battery design and its desired performance. The alkaline electrolyte aqueous solution can include a hydroxide as an ion-conducting component in an aqueous solution. Based on the total weight of the electrolyte, the concentration of the hydroxide in the electrolyte can be from about 25 weight percent (wt.%) to about 35wt.%. For example, based on the total weight of the electrolyte, the hydroxide concentration of the electrolyte can be from about 25wt.% to about 33wt.% or from about 25wt.% to about 32wt.%.
[0069] With regard to assembled alkaline cells, the concentration of ion-conducting components can be determined by collecting the total amount of electrolyte from assembled alkaline cells, such as AA or AAA alkaline cells. This can usually be achieved by removing separators, cathode and anode components and dissolving these components in a hydrochloric acid solution. Hydrogen peroxide can be added in a dropwise manner to assist the dissolution process. The dissolved solution can then be diluted to a specific volume to provide an analyte. The analyte can then be analyzed by an inductively coupled plasma (ICP) emission spectrometer such as JY Ultra Trace or its equivalent to determine the total positive ion concentration of the ion-conducting components within the analyte, such as potassium (K+) concentration in ppm. The total positive ion concentration determined from the analyte by ICP can be used to mathematically determine positive ions, such as the total weight of potassium (K+) in grams, and subsequently determine the total weight of ion-conducting components in the electrolyte solution of the sampled alkaline cell, such as potassium hydroxide (KOH) in grams. Based on the weight of the electrolyte, the concentration of the ion-conducting component of the electrolyte, such as potassium hydroxide (KOH), can be determined by dividing the total weight of the ion-conducting component by the weight of the analyte.
[0070] The alkaline electrolyte aqueous solution may also contain zinc oxide (ZnO). ZnO can be used to inhibit zinc corrosion within the anode. The concentration of ZnO contained within the electrolyte may be less than about 3 wt% of the electrolyte. For example, the ZnO concentration may be less than about 2 wt% of the electrolyte.
[0071] In an embodiment, the total weight of the alkaline electrolyte aqueous solution within an AA alkaline battery may be, for example, about 3.0 grams to about 4.0 grams, such as about 3.3 grams to about 3.8 grams or about 3.4 grams to about 3.6 grams. In an embodiment, the total weight of the alkaline electrolyte aqueous solution within an AAA alkaline battery may be, for example, about 1.0 gram to about 2.0 grams, such as about 1.2 grams to about 1.8 grams or about 1.4 grams to about 1.6 grams. Although the foregoing amounts are intended to be useful, one of ordinary skill in the art can readily determine the appropriate weight of the alkaline electrolyte aqueous solution required for other battery sizes, types, and configurations.
[0072] Cathode
[0073] The cathode 12 may include an electrochemically active cathode material, carbon particles, and optionally a binder. The electrolyte solution is also dispersed within the cathode 12. The weight percentages provided above and below are determined after the electrolyte solution has been dispersed.
[0074] The electrochemically active cathode material may include one or more manganese oxides. For example, the electrochemically active cathode material may include one or more manganese dioxides selected from one or more of the following group: electrolytic manganese dioxide (EMD), chemical manganese dioxide (CMD), high power electrolytic manganese dioxide (HP EMD), λ manganese dioxide, γ manganese dioxide, and β manganese dioxide. Other suitable electrochemically active cathode materials may be used, including but not limited to silver oxide, nickel oxide, silver nickel oxide, nickel oxyhydroxide, copper oxide, silver copper oxide, bismuth oxide, higher valent nickel, its alloys, and its mixtures. Nickel oxide may include nickel hydroxide, nickel oxyhydroxide, nickel oxyhydroxide coated with cobalt oxyhydroxide, delithiated layered lithium nickel oxide, partially delithiated layered lithium nickel oxide, and combinations thereof. Nickel oxyhydroxide may include β-nickel oxyhydroxide, γ-nickel oxyhydroxide, symbiotes of β-nickel oxyhydroxide, γ-nickel oxyhydroxide, nickel oxyhydroxide coated with cobalt oxyhydroxide, and mixtures thereof. Nickel oxyhydroxide coated with cobalt oxyhydroxide may include nickel oxyhydroxide coated with cobalt oxyhydroxide of β-nickel oxyhydroxide, nickel oxyhydroxide coated with cobalt oxyhydroxide of γ-nickel oxyhydroxide, symbiotes of β-nickel oxyhydroxide and γ-nickel oxyhydroxide coated with cobalt oxyhydroxide, and mixtures thereof. Nickel oxide may include partially delithiated layered nickel oxide having the chemical general formula Li 1-x H y NiO2, where 0.1 < x < 0.9 and 0.1 < y < 0.9. Nickel oxide may include a layered nickel oxide having the chemical general formula A x H y Ni1+a-z M z Partially delithiated layered nickel oxide of O2, where A includes an alkali metal; 0.08 ≤ x < 0.2; 0 ≤ y < 0.3; 0.02 ≤ a ≤ 0.2; M includes a transition metal or a main group metal, and 0 ≤ z ≤ 0.2, as disclosed in US-2018-0331361-A1, which is hereby incorporated by reference. The high-valent nickel can be, for example, a compound including tetravalent nickel, such as a compound having the general formula A x A' v Ni 1+a-z M z O2·nH2O, where A includes an alkali metal; A' includes an alkali metal different from A; M includes a transition metal or a non-transition metal; 0.04 ≤ x < 0.2; 0.03 ≤ v < 0.2; 0.02 ≤ a ≤ 0.2; 0 ≤ z < 0.2; and 0 < n < 2, as disclosed in US-2018-0331361-A1, which is hereby incorporated by reference.
[0075] EMD is usually manufactured by the direct electrolysis of manganese sulfate and a sulfuric acid bath. The manufacturing process of EMD and its properties are described in "Batteries", edited by Karl V. Kordesch, Marcel Dekker, Inc., New York, Volume 1, (1974), pages 433 - 488. CMD is usually made by a process known in the art as the "Sedema process", which is a chemical process disclosed in U.S. Patent No. 2,956,860 (Welsh). Battery-grade MnO2 can be produced by the Sedema process by using a reaction mixture of MnSO4 and an alkali metal chlorate such as NaClO3. Suitable manganese dioxides can be obtained from, for example, Tronox (Stamford, CT), Vibrantz Technologies (Houston, TX), Tosoh Corportation (Tokyo, Japan), Delta Manganese Ltd. (Mbombela, South Africa), and Xiangtan Electrochemical Scientific (Xiangtan, China).
[0076] Conventional battery-grade manganese dioxide-containing compositions do not have a true stoichiometric formula of MnO2, but are better represented by the formula MnO x, where x is typically between about 1.92 and 1.96, corresponding to a manganese value between about 3.84 and 3.92. Conventional EMDs typically have x values of about 1.95 or 1.96, corresponding to manganese values of 3.90 and 3.92, respectively. Conventional EMDs also have a true density of about 4.4 g / cm 3 and 4.6g / cm 3 between.
[0077] The carbon particles can be any conventional carbon particles used in the cathode. The carbon particles can be, for example, graphite particles. Graphite can be synthetic or non-synthetic, or a blend of synthetic and non-synthetic. Suitable graphite particles can be obtained from, for example, Nacional de Grafite (Sao Paulo, Brazil), Imerys Graphite & Carbon (Bodio, Switzerland) and Superior Graphite Company (Chicago, Illinois). The cathode can include, for example, carbon particles between about 3% by weight and about 7% by weight, for example, between about 4% by weight and about 6.5% by weight or about 2% by weight to about 5% by weight.
[0078] Carbon particles are included in the cathode to allow electrons to flow through the cathode. Lower levels of carbon particles enable higher levels of active material to be included in the cathode without increasing the volume of the battery cell or reducing the void volume (void volume must be maintained at or above a certain level to prevent internal pressure from rising too high when gas is generated in the battery cell).
[0079] The binder is stable in the presence of an electrochemically active cathode material. The binder generally has minimal swelling behavior in water. Minimizing the swelling amount of the binder maximizes the amount of electrochemically active cathode material in the cathode. In an embodiment, the swelling of the binder in water is no more than about 10%, no more than about 5%, or no more than about 3%. Examples of suitable binders include hydroxypropyl methylcellulose (HPMC), polyacrylates, polyvinyl alcohol (PVOH), polyethylene powders, polyacrylamides, portland cement, and fluorocarbon resins, such as PVDF and PTFE. An example of a polyethylene binder is sold under the trade name CoathyleneHA-1681 (available from Axalta Coating Systems, PA, Pennsylvania). The cathode may include, for example, a binder between about 0.1% by weight and about 1% by weight. Lower binder levels can include higher levels of active materials in the cathode.
[0080] The cathode 12 may include other additives. Examples of other cathode additives are described, for example, in U.S. Pat. Nos. 5,342,712; 5,698,315; 5,919,598; 5,997,775; and 7,351,499, which are hereby incorporated by reference. The cathode 12 may include, for example, about 0.2 wt % to about 2 wt % TiO2. The cathode may also include a surfactant. The surfactant will need to be compatible with the binder so as not to adversely affect the bonding ability. Examples of surfactants suitable for the cathode include, but are not limited to, anionic surfactants, amphoteric surfactants, and combinations thereof.
[0081] A non-limiting example of a surfactant suitable for use in the cathode may include diphenyl sulfonate or a derivative thereof. In one embodiment, the surfactant includes an anionic diphenyl sulfonate surfactant or a hydrocarbyl-substituted derivative thereof, wherein the hydrocarbyl group contains 1 to about 24, for example, 1 to about 12 carbon atoms. Specific examples include alkali metal alkyl diphenyl oxide disulfonates, such as sodium hexyl diphenyl oxide disulfonate, sodium decyl diphenyl oxide disulfonate, dodecyl diphenyl oxide disulfonic acid, sodium dodecyl diphenyl oxide disulfonate, n-decyl diphenyl oxide disulfonate, sodium n-decyl diphenyl oxide disulfonate, and sodium n-hexadecyl diphenyl oxide disulfonate. Diphenoxy sulfonate surfactants are marketed under the trade name DOWFAX TM (The Dow Chemical Company, MI) are commercially available and specifically include DOWFAX TM C6L, C10L, 2AO, 2A1, 2A1-D, 2EP, 3BO, 3B2, 3B2-D, 2000, 8390 and 8390-D.
[0082] The amount of electrochemically active cathode material in the cathode can be referred to as cathode loading. The cathode loading can vary according to the electrochemically active cathode material used in the battery and the cell size of the battery. For example, an AA battery with a manganese dioxide electrochemically active cathode material can have a cathode loading of at least 10.0 grams of manganese dioxide, for example, at least about 10.5 grams of manganese dioxide, between about 10.7 grams and about 11.5 grams of manganese dioxide, between about 10.7 grams and about 11.0 grams of manganese dioxide, between about 10.8 grams and about 11.2 grams of manganese dioxide, between about 10.9 grams and about 11.5 grams of manganese dioxide. For AAA batteries, the cathode loading can be between about 4.0 grams and about 6.0 grams of manganese dioxide. For AAAA batteries, the cathode loading can be between about 2.0 grams and about 3.0 grams of manganese dioxide. For C batteries, the cathode loading can be between about 25.0 grams and about 29.0 grams of manganese dioxide. For a D cell, the cathode loading may be between about 54.0 grams and about 70.0 grams of manganese dioxide.
[0083] The cathode should have sufficient dry density to ensure good conductivity. The cathode dry density can be between about 2.0 g / cm 2 With 3.5g / cm 2 Between, or between about 2.4g / cm 2 With 3.3g / cm 2 between.
[0084] Partition
[0085] Separator 16 can have any conventional design of battery separator. In some embodiments, separator can comprise woven or nonwoven paper or fabric. Separator can comprise a layer of, for example, cellophane combined with a layer of nonwoven material. Cellophane layer can be adjacent to cathode 12 or anode 14. Separator can also comprise additional nonwoven material layer. Separator material can be thin. For example, dry thickness of separator can be less than 150 micrometers (micrometer / micron). For example, dry thickness of separator can be less than 100 micrometers, for example, about 70 micrometers to about 90 micrometers or about 70 micrometers to about 75 micrometers. Basis weight of separator is 40g / m 2 or less, for example, about 15 g / m 2 About 40g / m 2 or about 20g / m 2 About 30g / m 2 .
[0086] The battery case 18 can be any conventional case commonly used for primary alkaline batteries. The battery case can be made of metal, such as nickel-plated cold rolled steel. The case generally comprises an inner conductive metal wall and an outer non-conductive material, such as heat shrinkable plastic. An additional conductive material layer can be arranged between the inner wall of the battery case 18 and the cathode 12. The layer can be arranged along the inner surface of the wall, along the circumference of the cathode 12, or along both. The conductive layer can be applied to the inner wall of the battery, for example, as a coating or dispersion comprising a carbonaceous material, a polymer binder, and one or more solvents. The carbonaceous material can be carbon particles, such as carbon black, partially graphitized carbon black, or graphite particles.
[0087] Anode current collector 20 passes through seal 22 extending into anode 14. Current collector 20 is made of a suitable metal such as brass or brass-plated steel. The upper end of current collector 20 is in electrical contact with negative electrode cap 24. Seal 22 can be made of, for example, a thermoplastic material such as nylon.
[0088] The cell 10 may be assembled using conventional methods and sealed by a mechanical crimping process.
[0089] The compositions and methods according to the present disclosure may be better understood in light of the following examples, which are intended only to illustrate the compositions and methods of the present disclosure and are not meant to limit the scope thereof in any way.
[0090] Performance Testing Methods
[0091] The performance tests included a discharge performance test, which may be referred to as the ANSI / IEC Motor / Toy Test (Toy Test). The Toy Test protocol included applying a constant load of 3.9 ohms for 1 hour, allowing the battery to rest for a predetermined period of time, and then applying the load again. The cycle was repeated until a cutoff voltage of 0.8 volts was reached. The results are reported in service hours (or hours of applied load). In the modified protocol results shown in Example 2, the battery rested for a period of 12 hours. Typically, as performed in Example 3, a 23 hour rest was used, but the results were generally the same with a shorter rest period. A Maccor test system was used.
[0092] The performance test also includes a discharge performance test, which can be referred to as a digital camera (DigiCam) test. The digital camera test is a pulse test scheme that includes discharging the battery using high-power and medium-power pulse discharge cycles. Each discharge cycle consists of a combination of two discharge schemes, including a 1.5-watt high-power pulse for a period of 2 seconds, followed by a 650mW medium-power pulse for a period of 28 seconds. This combination of discharge schemes is repeated ten times (i.e., a total of 5 minutes), and then the battery is allowed to rest for a period of fifty-five minutes. Repeat the combination of high-power and medium-power discharge pulses and rest periods (i.e., 1 hour / cycle) until a cut-off voltage of 1.05 volts is reached. The number of cycles required to reach the cut-off voltage is reported in the form of "pulses" or "pictures". The reported number of pulses consists of the total number of 1.5-watt high-power pulses, which corresponds to the total number of discharge cycles. The Digicam discharge test is considered to be a high-rate intermittent discharge test for conventional AA batteries. Use a Maccor test system.
[0093] The performance tests also included a discharge performance test, which may be referred to as a 3.9 ohm continuous discharge test. The 3.9 ohm continuous discharge test protocol included discharging the battery to support a constant load of 3.9 ohms until a cutoff voltage of 0.8 volts was reached. The results are reported in service hours (or hours with applied load). A Maccor test system was used.
[0094] The performance test further includes a discharge performance test, which may be referred to as a pulse load voltage test. The pulse load voltage test protocol includes discharging the battery for one second at a current draw of 80 mA and then measuring the voltage immediately. A Maccor test system is used.
[0095] The performance tests included a discharge performance test, which may be referred to as an intermittent 3.9 ohm discharge test. The battery cell was discharged at 3.9 ohms for 1 hour on a Maccor test apparatus, rested for a period of 12 hours, and then cycled again for a specified number of pulses. The discharge curve shows the relationship between voltage and capacity and demonstrates the relative differences in capacity (or discharge rate) between battery cells. A Maccor test system was used.
[0096] Examples
[0097] Example 1
[0098] Ethoxylated naphthol phosphates were synthesized by reacting ethoxylated naphthol (Angene International Limited, Nanjing, China) and phosphorus pentoxide (PO) in a 12:1 ratio in a beaker on a hot plate in an argon glove box with stirring. Different ethoxylated aromatic species can be readily synthesized using known ethoxylation procedures and reacted similarly with phosphorus pentoxide.
[0099] A 3% weakly alkaline solution of the orange viscous product was prepared for addition to the zinc anode. Advantageously, the material exhibits greater water solubility than the polyoxyethylene dinonylphenyl ether phosphates typically used in anode compositions.
[0100] Surfactant was analyzed and characterized by 1H and 31P NMR. The degree of ethoxylation was determined by setting the integral reference of the aromatic region of the 1H NMR spectrum and dividing the sum of the region from 3.2 to 4.2ppm by 4. The degree of ethoxylation was determined to be 14. The mol% of each phosphorus species was determined by integrating the peak area of 31P NMR collected using reverse gating decoupling. 31P NMR analysis showed that the surfactant contained 75mol% of monoester of phosphoric acid, 18mol% of diester of phosphoric acid and 7% of residual phosphoric acid.
[0101] Example 2
[0102] AA batteries with the same components except for the surfactant composition of the anode were prepared. The surfactant concentration in the anode composition is reported relative to the weight of the zinc metal particles. The anode composition was prepared using different concentrations of the surfactant synthesized in Example 1, and the assembled battery was compared with a comparative battery example, which included an anode composition containing polyoxyethylene dinonylphenyl ether phosphate, as described above, which is a commonly used surfactant in anode compositions in commercially available batteries. As described above, the battery was stored at room temperature and then tested for performance. One battery cell was tested per group. The results are shown in Table 1 below.
[0103]
[0104] Example 2 shows that cells Examples A, B, and C according to the present invention exhibit comparable Digicam results, fast toy results, and continuous discharge results compared to Comparative Example D, indicating that the amount of zinc surface coverage provided by the surfactants of the present disclosure is comparable to the amount of surface coverage provided by the commercial comparative surfactants, despite containing significantly and surprisingly low surfactant concentrations. These results surprisingly show that the cell performance is similar at levels approaching 20% relative to the amount of surfactant used in the comparative examples. Thus, Example 2 shows that the performance of the cells of the present disclosure containing an anode including a surfactant according to the present disclosure is at least as good as the comparative cells, while containing significantly less surfactant than the comparative cells, and not containing nonylphenol functional groups.
[0105] Because the surfactants of the present disclosure can advantageously coat the anode surface with significantly less surfactant than commercial surfactants, less surfactant must be removed from the surface of the anode to allow the discharge reaction to proceed. Without intending to be bound by theory, it is believed that the surfactants of the present disclosure have greater solubility in alkaline electrolytes than commercial surfactants. As a result, advantageously, less energy is required to remove the surfactants of the present disclosure from the anode surface.
[0106] Example 3
[0107] AA batteries with the same components except for the surfactant composition of the anode were prepared. The surfactant concentration in the anode composition is reported relative to the weight of the zinc metal particles. An anode composition was prepared using the surfactant synthesized in Example 1, and the assembled battery was compared with a comparative battery example, which included an anode composition containing polyoxyethylene dinonylphenyl ether phosphate, as described above, which is a commonly used surfactant in anode compositions in commercially available batteries. As described above, the battery was stored at room temperature and then tested for performance. Two battery cells were tested per group, and the average values are reported as follows. The results are shown in Table 2 below.
[0108]
[0109] Example 3 shows that Cell Example E exhibits comparable Digicam results, Fast Toy results, and Pulse Load Voltage results compared to Comparative Cell Example F, indicating that the amount of zinc surface coverage provided by the surfactants of the present disclosure is comparable to the amount of surface coverage provided by the commercial comparative surfactants, despite being incorporated at significantly and surprisingly low surfactant concentrations. Similar to the results shown in Example 2, these results surprisingly show that the cell performance is similar at levels approaching 20% relative to the amount of surfactant used in the corresponding comparative examples. Thus, Example 3 further demonstrates that the performance of the cells of the present disclosure including an anode of a surfactant according to the present disclosure is at least as good as the comparative cells while containing significantly less surfactant than the comparative cells.
[0110] Example 4
[0111] AA cells were prepared having the same components except for the surfactant composition of the anode. In this example, a cell including an anode composition comprising a surfactant according to the invention was compared to a cell including an anode that did not include a surfactant.
[0112] Figure 2 Continuous discharge at 3.9 ohms for a AA cell including an anode without surfactant additive relative to a AA cell including an anode including a surfactant according to the present invention, specifically an ethoxylated naphthol phosphate prepared according to Example 1 is shown. Figure 2 It is shown that AA cells including anodes without surfactant additives experience premature polarization relative to AA cells including anodes including surfactants according to the present invention.
[0113] Figure 3 The intermittent discharge of a AA cell including an anode without additive relative to a AA cell including an anode including a surfactant according to the present invention, specifically an ethoxylated naphthol phosphate prepared according to Example 1, is shown. Figure 3 It is shown that AA battery cells including anodes containing surfactants according to the present invention exhibit greater capacity relative to AA battery cells including anodes without surfactant additives.
[0114] The foregoing description has been given only for clearness of understanding, and no unnecessary limitations should be understood therefrom, since modifications within the scope of the disclosure may be obvious to those skilled in the art.
[0115] All patents, publications, and references cited herein are hereby incorporated by reference in their entirety. In the event of a conflict between the present disclosure and the incorporated patents, publications, and references, the present disclosure shall control.
Claims
1. An anode composition comprising: Zinc or zinc alloys; as well as Surfactant of formula (I): wherein R1 comprises an aryl group; y is 1 or 2; x is an integer from 2 to 30; and n is an integer of 2-6.
2. The anode composition of claim 1, wherein R1 comprises one or more aryl groups selected from the group consisting of naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, and perylenyl.
3. The anode composition according to claim 1 or claim 2, wherein n is an integer from 2 to 3.
4. The anode composition according to any one of the preceding claims, wherein n is 2.
5. The anode composition of claim 1 or claim 2, wherein n is 3.
6. The anode composition of any preceding claim, wherein the surfactant of formula (I) comprises a mixture of surfactants of formula (I).
7. The anode composition according to any one of the preceding claims, wherein the surfactant of formula (I) comprises a mixture of phosphoric acid monoester and phosphoric acid diester surfactants according to formula (I).
8. The anode composition of any preceding claim, which is free of nonylphenol functional groups.
9. The anode composition of claim 6 or claim 7, wherein for the mixture of surfactants of formula (I), the average x is an integer from 6 to 16, from 8 to 16, or from 8 to 14.
10. The anode composition of any preceding claim, wherein R1 is 2-naphthyl.
11. The anode composition of any of the preceding claims, wherein the surfactant according to formula (I) is provided in an amount of about 10 ppm to about 75 ppm, about 10 ppm to about 65 ppm, about 10 ppm to about 55 ppm, about 10 ppm to about 50 ppm, about 20 ppm to about 50 ppm, or about 20 ppm to about 45 ppm, relative to the amount of zinc or zinc alloy.
12. An alkaline battery comprising: an anode comprising the anode composition according to any one of claims 1 to 11; cathode; a separator between the anode and the cathode; as well as Alkaline electrolyte.
13. The battery of claim 12, wherein the alkaline electrolyte comprises hydroxide in an amount between about 25 weight percent (wt. %) and about 40 wt. %, based on the weight of the electrolyte in the battery.
14. A battery according to claim 12 or claim 13, wherein the cathode comprises one or more manganese oxides, such as one or more manganese dioxides, selected from one or more of the following groups: electrolytic manganese dioxide (EMD), chemical manganese dioxide (CMD), high power electrolytic manganese dioxide (HP EMD), lambda manganese dioxide, gamma manganese dioxide and beta manganese dioxide.
15. The battery of any one of claims 12 to 14, wherein the cathode comprises one or more electrochemically active cathode materials selected from one or more of the following group: silver oxide, nickel oxide, silver nickel oxide, nickel oxyhydroxide, copper oxide, silver copper oxide, bismuth oxide, high-valent nickel, and alloys thereof.
16. The battery of claim 15, wherein the cathode comprises one or more nickel oxides selected from the group consisting of nickel hydroxide, nickel oxyhydroxide, nickel oxyhydroxide coated with cobalt oxyhydroxide, delithiated layered lithium nickel oxide, partially delithiated layered lithium nickel oxide, and combinations thereof.
17. A method for preparing a battery anode, the method comprising: Mix zinc or zinc alloy with a surfactant of formula (I): wherein R1 is selected from aryl; y is 1 or 2; x is an integer from 2 to 30; and n is an integer of 2-6.
18. A method for preparing a battery, the method comprising: An anode comprising zinc or a zinc alloy and a surfactant of formula (I) is incorporated into a cell: Wherein R1 is selected from aryl and C1-C12 alkyl; y is 1 or 2; x is an integer from 2 to 30; and n is an integer of 2-6.
19. The method of claim 18, wherein the surfactant according to formula (I) is provided in an amount ranging from about 10 ppm to about 75 ppm, from about 10 ppm to about 65 ppm, from about 10 ppm to about 55 ppm, from about 10 ppm to about 50 ppm, from about 20 ppm to about 50 ppm, or from about 20 ppm to about 45 ppm, relative to the amount of zinc or zinc alloy in the anode composition.
20. An anode composition comprising: Zinc or zinc alloys; as well as Surfactant of formula (I): wherein R is methyl or hydrogen; x is an integer from 2 to 30; and Rings 1 and 2 represent a coupled ring system comprising at least 10 ring carbons.
21. The anode composition of claim 20, wherein the coupled ring system comprises naphthyl, fluorenyl, anthracenyl, phenanthrenyl, naphthacene, benzo[a]anthryl, pyrenyl, perylenyl, biphenyl, or bicyclohexyl.
22. The anode composition of claim 20 or claim 21, wherein n is an integer from 2 to 3.
23. The anode composition of any one of claims 20 to 22, wherein n is 2.
24. The anode composition of any one of claims 20 to 22, wherein n is 3.
25. The anode composition of any one of claims 20 to 24, wherein the surfactant of formula (II) comprises a mixture of surfactants of formula (II).
26. The anode composition of any one of claims 20 to 25, which is free of nonylphenol functional groups.
27. The anode composition of claim 25, wherein for the mixture of surfactants of formula (II), the average x is an integer from 6 to 16, from 8 to 16, or from 8 to 14.
28. The anode composition of any one of claims 20 to 27, wherein R1 is 2-naphthyl.
29. The anode composition of any one of claims 20 to 28, wherein the surfactant according to formula (I) is provided in an amount of about 10 ppm to about 75 ppm, about 10 ppm to about 65 ppm, about 10 ppm to about 55 ppm, about 10 ppm to about 50 ppm, about 20 ppm to about 50 ppm, or about 20 ppm to about 45 ppm, relative to the amount of zinc or zinc alloy.
30. An alkaline battery comprising: an anode comprising the anode composition according to any one of claims 20 to 29; cathode; a separator between the anode and the cathode; as well as Alkaline electrolyte.
31. The battery of claim 30, wherein the alkaline electrolyte comprises hydroxide in an amount between about 25 weight percent (wt.%) and about 40 wt.%, based on the weight of the electrolyte in the battery.
32. A battery according to claim 30 or claim 31, wherein the cathode comprises one or more manganese oxides, such as one or more manganese dioxides, selected from one or more of the following groups: electrolytic manganese dioxide (EMD), chemical manganese dioxide (CMD), high power electrolytic manganese dioxide (HP EMD), lambda manganese dioxide, gamma manganese dioxide and beta manganese dioxide.
33. A battery according to any one of claims 30 to 32, wherein the cathode comprises one or more electrochemically active cathode materials selected from one or more of the following groups: silver oxide, nickel oxide, silver nickel oxide, nickel oxyhydroxide, copper oxide, silver copper oxide, bismuth oxide, high-valent nickel and alloys thereof.
34. A battery according to claim 33, wherein the cathode comprises one or more nickel oxides, the one or more nickel oxides selected from one or more of the following groups: nickel hydroxide, nickel oxyhydroxide, nickel oxyhydroxide coated with cobalt oxyhydroxide, delithiated layered lithium nickel oxide, partially delithiated layered lithium nickel oxide, and combinations thereof.
35. A method for preparing a battery anode, the method comprising: Mix zinc or zinc alloy with a surfactant of formula (I): wherein R is methyl or hydrogen; x is an integer from 2 to 30; and Rings 1 and 2 represent a coupled ring system comprising at least 10 ring carbons.
36. A method for preparing a battery, the method comprising: An anode comprising zinc or a zinc alloy and a surfactant of formula (II) is incorporated into a cell: wherein R is methyl or hydrogen; x is an integer from 2 to 30; and Rings 1 and 2 represent a coupled ring system comprising at least 10 ring carbons.
37. The method of claim 36, wherein the surfactant according to formula (I) is provided in an amount ranging from about 10 ppm to about 75 ppm, from about 10 ppm to about 65 ppm, from about 10 ppm to about 55 ppm, from about 10 ppm to about 50 ppm, from about 20 ppm to about 50 ppm, or from about 20 ppm to about 45 ppm, relative to the amount of zinc or zinc alloy in the anode composition.
Citation Information
Patent Citations
Alkaline battery including nickel oxyhydroxide cathode and zinc anode
US20070248879A1
Battery including beta-delithiated layered nickel oxide electrochemically active cathode material
US20180331361A1
Process for producing manganese dioxide
US2956860A
Additives for primary electrochemical cells having manganese dioxide cathodes
US5342712A
Electrically-conductive colorless transparent barium sulfate filler
US5698315A